Bimbingan Masuk Perguruan Tinggi yang Sesuai Minat dan Bakat Siswa Generasi Z: College Entrance Guidance that Matches the Interests and Talents of Generation Z Students - Syafril Syafril; Tania Jannah; Andi Makkulawu Panyiwi Kessi; Liawati Liawati (Pengabdian Pendidikan Indonesia, 2026)
This Community Service (PKM) activity is one of the obligations for a lecturer to fulfill the Tridharma of Higher Education, namely teaching, scientific research, and Community Service. This Community Service (PKM) was carried out through collaboration between Madrasah Aliyah Negeri 1 Marabahan and the lecturers, in the context of College Entrance Guidance that Suits the Interests and Talents of Generation Z Students. This guidance aims to help grade XII students of Madrasah Aliyah Negeri 1 Marabahan choose a college that suits their abilities and capabilities upon graduation. Choosing a college is not just an administrative step after graduating from school, but a major decision that shapes the direction of one's life. Choosing a college to study after graduating from high school or an equivalent is not easy for some students. The guidance will provide students with important information when they enter college later. The method used in this service was through socialization, lively presentations, discussions, and question-and-answer sessions. The results of this service are expected to prepare students for the desired level of higher education. College is one level of education that can lead to a better future.